Effects of Probiotic Supplementation on TGF-β1, TGF-β2, and IgA Levels in the Milk of Japanese Women: An Open-Label Pilot Study - Takahashi, Tomoki; Fukudome, Hirofumi; Ueno, Hiroshi M.; Watanabe-Matsuhashi, Shiomi; Nakano, Taku; Kobayashi, Toshiya; Ishimaru, Kayoko; Nakao, Atsuhito (Frontiers in Nutrition, 2019)
Abstract Background: Dietary probiotics supplementation in lactating mothers may help prevent allergic disease in infants. However, owing to a lack of consistency in nutritional and safety outcomes associated with probiotics, this topic remains controversial. Methods: In this open-label pilot trial conducted between April 2013 and December 2013, we evaluated the safety of probiotic supplementation with 5 × 109 CFU of Lactobacillus casei LC5, 5 × 109 CFU of Bifidobacterium longum BG7, and 2 × 108 CFU of Bacillus coagulans SANK70258 in lactating women who exhibited allergies for 2 months (1-3 months postpartum); we also evaluated the effects of probiotic supplementation on transforming growth factor-β (TGF-β) and immunoglobulin A (IgA) levels in human milk. Participants self-selected to join the probiotic (n = 41; age [median (interquartile range [IQR]), y] 33 [27-39], body mass index [BMI] [median (IQR), kg/m2] 21.8 [19.5-22.8]) or no supplementation control group (n = 19; age [median (IQR), y] 33 [23-43], BMI [median (IQR), kg/m2) 19.6 [18.4-22.1]). Probiotics (three tablets) received were taken as daily supplements. Milk samples were collected at one, 2, and 3 months postpartum, and TGF-β1, TGF-β2, and IgA levels were measured. Results: No adverse effects were observed in the probiotic group, according to the self-recorded diary during the study period. Milk IgA decreased with increasing postpartum months in both groups. In contrast, TGF-β1 and β2 were not affected by lactation periods, and showed different patterns over time between the two groups. TGF-β1, TGF-β1, and IgA levels were significantly correlated at baseline (respectively p < 0.05). However, the correlation between TGF-β1 and IgA became non-significant by the end of the intervention (p = 0.063). Conclusion: Altogether, probiotic supplementation was tolerated with respect to no dropout and 91.5% adherence. Although probiotic supplementation might affect human milk TGF-β levels, a positive effect of probiotic supplementation was not entirely supported. Future placebo-controlled studies are needed to further support the efficacy and safety of probiotic supplementation.